Do Migrants Facilitate Internationalization? A Review of the Literature - Andreas Hatzigeorgiou; Magnus Lodefalk (Örebro University School of Business, 2018)
How migration relates to internationalization has been a prominent question in international economics for a long time and its relevance for policy has increased with the amplified political focus on migration. But the role of migration for internationalization is not as obvious as the standard theory suggests, and tightening migration could have unexpected consequences for both developing and developed countries. In this paper we review and discuss over 100 papers published about migrants' role in international trade and foreign direct investment, from pioneering country-level studies to nascent firm-level studies that utilize employer-employee data. To our knowledge, this is the first paper offering a wide-ranging review of the different strands of theory on the relationship between migration and internationalization, as well as new empirical findings. Although the evidence suggests that migration can facilitate internationalization, we also note substantial gaps and inconsistencies in the extant literature. The aim of this paper is to encourage future research and assist policymakers in their efforts to promote internationalization, and better understand the economic effects of changes in migration policy.
Keywords: D20; D80; F14; F16; F22; F23; J61; 330; Migration; networks; information; trade; foreign direct investment